Derivational and Inflectional Morphemes of Balinese Language Spoken in Dausa - Sari, Nyoman Arina Putri; Ramendra, Dewa Putu; Budasi, I Gede (STKIP Agama Hindu Singaraja, 2024)
This study aimed at describing the prefixes and suffixes of the Balinesse language spoken in Dausa, Kintamani Sub-District, Bangli district, and Banjar Tengah Regency in Bali. The prefixes and suffixes described in this study belong to the one categorized as derivational and inflectional morphemes. This descriptive qualitative research involved three informants as the source of study data. They were selected based on a set of criteria suggested by Samarin (1998). The data were collected based on three techniques, namely: observation, recording technique, and interview. The researcher studied Dausa, observing, recording, and noting informants' data. Then transcribed, categorized, and translated the data into Indonesian, identified prefixes and suffixes, formulating rules for derivational and inflectional morphemes based on the data display. The results of the study show that there are seven kinds of prefixes found in the language. The prefixes include bΛ-, bǝ-, mɅ-, n-, ŋ-, ñ-, and mә-, and there are five kinds of suffixes which include -Ʌŋ, -In, -Ʌn, -Ʌ, and -ē. Among them, there are three kinds of prefixes: mɅ-, ŋ-, and mә-, and there are four kinds of suffixes: -Ʌŋ, -In, -Ʌn, and -Ʌ that are categorized as derivational morphemes. There were five kinds of prefixes: bΛ-, bǝ-, ŋ-, ñ-, mǝ-, and five kinds of suffixes: -ē, -Ʌŋ, -in, -Ʌn, and -Ʌ which are categorized as inflectional morphemes. The study informs academics about Balinese morphemes.